2022
DOI: 10.1021/acs.macromol.1c02367
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Gas Transport in Polymer-Grafted Nanoparticle Assemblies

Abstract: We rationalize the unusual gas transport behavior of polymer-grafted nanoparticle (GNP) membranes. While gas permeabilities depend specifically on the chemistry of the polymers considered, we focus here on permeabilities relative to the corresponding pure polymer, which show interesting, “universal” behavior. For a given NP radius, R c, and for large enough areal grafting densities, σ, to be in the dense brush regime, we find that gas permeability enhancements display a maximum as a function of the graft chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…18,39 In gas transport applications, for example, it has been found that increasing molecular weight for short chains increasingly enhances gas permeability in GNPs relative to the neat polymers, but beyond a critical MW g , the normalized gas permeability enhancements decrease, which is dependent on grafting density, graft chain chemistry, and core size. 18,24 We propose that this can be rationalized by postulating that the dry zone with stretched, aligned chains has a faster intrinsic diffusivity. Computational work by Bobbili and Milner has shown that stretched, aligned chains have lower monomeric friction coefficients, which support this conjecture of faster diffusivity in the dry zones.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,39 In gas transport applications, for example, it has been found that increasing molecular weight for short chains increasingly enhances gas permeability in GNPs relative to the neat polymers, but beyond a critical MW g , the normalized gas permeability enhancements decrease, which is dependent on grafting density, graft chain chemistry, and core size. 18,24 We propose that this can be rationalized by postulating that the dry zone with stretched, aligned chains has a faster intrinsic diffusivity. Computational work by Bobbili and Milner has shown that stretched, aligned chains have lower monomeric friction coefficients, which support this conjecture of faster diffusivity in the dry zones.…”
Section: Resultsmentioning
confidence: 99%
“…Given these studies and the predicted presence of both a dry and an interpenetrated brush layer in all the GNPs tested in the gas permeation experiments of Bilchak et al, it is still unclear why these materials display a gas permeability enhancement relative to the neat polymer and a permeability maximum at a MW g of ∼100 kDa for a grafting density of 0.47 chains/nm 2 . , To shed light on this situation, we study GNP packing as a function of the graft chain length (at fixed grafting density) using small-angle X-ray scattering (SAXS). The data obtained on poly­(methyl acrylate)-grafted silica NP films (PMA- g -SiO 2 ) were then analyzed using the Percus–Yevick hard sphere model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We presume that the limited size of vesicles of ∼80 nm AuNCs might be related to the geometric frustration due to the faceting effect, resembling the packing of viral capsids. 40 The formation of vesicles was associated with a redshift of their LSPR peak from ∼535 nm to ∼680 nm and a noticeable broadening of these peaks in the UV-visible spectra (Fig. 3f).…”
Section: Resultsmentioning
confidence: 91%
“…34 Furthermore, even for the longest polymer ligands used in our experiments, their length (∼20 nm) is not sufficient for forming a spherical corona on the surface of the NCs. 40 Thus, we presume that the interplay between cubic shape and anisotropic distribution of polymer ligands results in the different packing modes of NCs in the vesicular membranes.…”
Section: Resultsmentioning
confidence: 96%